2023
DOI: 10.1186/s12885-023-10589-9
|View full text |Cite
|
Sign up to set email alerts
|

1,5-Anhydroglucitol promotes pre-B acute lymphocytic leukemia progression by driving glycolysis and reactive oxygen species formation

Abstract: Background Precursor B-cell acute lymphoblastic leukemia (pre-B ALL) is the most common hematological malignancy in children. Cellular metabolic reorganization is closely related to the progression and treatment of leukemia. We found that the level of 1,5-anhydroglucitol (1,5-AG), which is structurally similar to glucose, was elevated in children with pre-B ALL. However, the effect of 1,5-AG on pre-B ALL was unclear. Here, we aimed to reveal the roles and mechanisms of 1,5-AG in pre-B ALL progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The rapid uptake of glucose is accompanied by an increased rate of glycolysis. In precursor B-cell acute lymphoblastic leukemia cells, the glucose analog 1,5-anhydroglucitol interrupts mitochondrial respiration by up-regulating pyruvate dehydrogenase kinase 4 (PDK4), thereby increasing the rate of glycolysis, and enhanced glycolysis leads to oxidative stress in tumor cells by increasing ROS levels [ 76 , 77 ]. Additionally, the decreased O 2 − level under hypoxia conditions inhibits the AMP-activated protein kinase (AMPK) activation and shifts metabolism from glycolysis to oxidative phosphorylation [ 78 ].…”
Section: Ros Levels In Cancer Cells and Cancer Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The rapid uptake of glucose is accompanied by an increased rate of glycolysis. In precursor B-cell acute lymphoblastic leukemia cells, the glucose analog 1,5-anhydroglucitol interrupts mitochondrial respiration by up-regulating pyruvate dehydrogenase kinase 4 (PDK4), thereby increasing the rate of glycolysis, and enhanced glycolysis leads to oxidative stress in tumor cells by increasing ROS levels [ 76 , 77 ]. Additionally, the decreased O 2 − level under hypoxia conditions inhibits the AMP-activated protein kinase (AMPK) activation and shifts metabolism from glycolysis to oxidative phosphorylation [ 78 ].…”
Section: Ros Levels In Cancer Cells and Cancer Developmentmentioning
confidence: 99%
“…It promotes the proliferation of acute myeloid leukemia by up-regulating the expression of 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase (PFKFB3), a key glycolytic regulator [ 92 ]. Furthermore, elevated glycolysis levels can promote the progression of precursor B-cell acute lymphocytic leukemia (pre-B AML) by activating MAPK/ERK pathways by increasing intracellular ROS levels [ 77 ]. The above research studies have shown that increased ROS accumulation can promote tumor progression through a variety of signaling pathways ( Figure 2 ).…”
Section: Ros Levels In Cancer Cells and Cancer Developmentmentioning
confidence: 99%
“…Blood glucose fluctuation could potentially have a crucial role in the advancement of coronary heart disease (CHD) patients [ 7 ]. 1,5-anhydroglucitol (1,5-AG) levels drop quickly with urinary glucose excretion, indicating glucose status over the past two weeks [ 8 ]. Recent research have found that 1,5-AG may provide a meaningful addition to glycosylated hemoglobin (Hb1Ac) testing, indicating short-term blood glucose status in contrast to traditional glucose markers [ 9 ].…”
Section: Introductionmentioning
confidence: 99%